Outport “Girls in Service”: Newfoundland in the 1920s and 1930s - Kealey, Linda (Acadiensis, 2014)
Interviews with former domestic servants as well as published memoirs provide a glimpse into the backgrounds, work lives, and migration patterns of young Newfoundland women who worked in service in St. John’s and smaller communities during the 1920s and 1930s. Migration from outport communities into domestic service work was a common experience for young women with few other options. “Girls in service” found positions not only in the homes of the wealthy but also in middle class and some skilled working class households. Domestics reported a sense of “difference” from their employers and engaged in a variety of strategies to resist exploitation.